Modeling and analysis for magnetic dipole impact in nonlinear thermally radiating Carreau nanofluid flow subject to heat generation - Waqas, Muhammad; Jabeen, Shagufta; Hayat, Tasawar; Khan, M. Ijaz; Alsaedi, Ahmed (Journal of magnetism and magnetic materials, 2019)
•Flow of Carreau nanofluid persuaded by magnetic dipole is modeled.•Buongiorno model for nanomaterials is taken into account for modeling.•Heat transfer captures nonlinear thermal radiation and heat generation effects.•Shooting scheme is implemented to compute the nonlinear systems.•The results are plotted and interpreted. Investigation regarding magnetic nanoparticles suspensions and their flow characteristics and the application prospects is active research area. Especially the biomedical utilizations and analysis about rheological aspects of such materials acquired great motivation. Magneto nanoparticles has meaningful impact on magneto-viscous behavior of ferroliquids which lead to stable viscosity alterations and manifestation of viscoelastic properties in fluids. Keeping such significance of ferroliquids in view our interest here is to elaborate nonlinear radiation impact in stretching flow subject to magnetic dipole. Rheological relations of Carreau material are employed for flow formulation. Buongiorno nanoliquid model elaborating thermophoretic and Brownian movement characteristics is employed for modeling and analysis. Besides the heat generation and viscous dissipation aspects are also accounted. The well-known Shooting scheme is implemented to compute the nonlinear systems. Impacts of sundry variables are described through graphical outcomes and numeric data. Our results reveal decay in velocity field subjected to larger ferrohydrodynamic interaction variable whereas thermal field increments when ferrohydrodynamic interaction variable is increased.